2021
DOI: 10.1177/17531934211029543
|View full text |Cite
|
Sign up to set email alerts
|

Important updates of finger fractures, entrapment neuropathies and wide-awake surgery of the upper extremity

Abstract: Hand surgery is rapidly changing. The wide-awake approach, minimum dissection surgery and early protected movement have changed many things. This is an update of some of the important changes regarding early protected movement with K-wired finger fracture management, simplification of nerve decompression surgery, such as elbow median and ulnar nerve releases, and some new areas in performing surgery with wide-awake local anaesthesia without tourniquet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Additionally, the radiological findings showed that bones healed in both groups by approximately 5 weeks, with no significant difference. However, outcomes determined from X-ray images do not always correlate with clinical healing [19], necessitating the consideration of clinical signs like the absence of tenderness on the fracture line as well [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the radiological findings showed that bones healed in both groups by approximately 5 weeks, with no significant difference. However, outcomes determined from X-ray images do not always correlate with clinical healing [19], necessitating the consideration of clinical signs like the absence of tenderness on the fracture line as well [20,21].…”
Section: Discussionmentioning
confidence: 99%